Microstructure and Mechanical Properties in Thermally Treated Cr-Mn-Cu Stainless Steel Welds - Lawal, Taiwo Folorunsho; Amuda, Muhammed Olawale Hakeem; Omonua, Fabian Sunday; Enumah, Kingsley Somtomchukwu (International Journal of Integrated Engineering, 2020)
In the present investigation, the mechanical properties in Cr-Mn-Cu austenitic stainless steel subjected to pre-weld and post-weld thermal treatments were characterized relative to microstructural features in the welds. Characterisation of microstructure evolution in the thermally treated welds indicated the development of refined cellular/dendritic structure relative to elongated columnar dendritic microstructure in the as-welded austenitic stainless steel. Specifically, pre-welds exhibited coarse grain morphology in contrast to refined morphology in post thermally treated welds. The contrast in grain morphology in the pre-weld and post-weld thermally treated welds was attributed to the differential cooling rates in these different thermal treatment conditions. Hardness value in the thermally treated welds decreases with increasing heat input across the various zones of the weld suggesting the development of equilibrium structure in welds subjected to either pre or post-weld thermal treatment. The highest value was however obtained in post-thermally treated welds. Tensile strength was highest in pre-weld thermally treated coupons at 953 MPa  followed by as-welded coupons at 947 MPa  and the least in post-weld thermally treated coupons at 921 MPa. A major finding from the investigation was that tensile strength decreases with increasing heat input across the process parameters considered irrespective of the thermal treatment conditions. This trend was in concord with the trend established in literature